2024
DOI: 10.26907/2542-064x.2023.4.688-700
|View full text |Cite
|
Sign up to set email alerts
|

Using Ichnofossils to Correlate Oil-Bearing Deposits in the Devonian Clastic Succession (Pashyian and Timanian Horizons) of the South Tatar Arch

D. N. Miftakhutdinova

Abstract: This article outlines the results of the first-ever ichnological study of the Middle Devonian clastic succession in the South Tatar Arch. The analysis of the stratigraphic distribution of trace fossils in the boreholes revealed several levels with biogenic structures such as ichnofossils and bioturbation, which proved useful for the correlation of the boreholes. The boundary interval of the Pashyian and Timanian Horizons is made up by a succession of three layers: bioturbated siltstones with Spirophyton burrow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…Finds of soft tissues of lingulids favour dysaerobic conditions. Lingulid burrows of reduced length (5-10 mm instead of 50-70 mm) were also found here (Miftakhutdinova, 2023), indicating that the primary sediment was compacted.…”
Section: Discussionsupporting
confidence: 53%
See 4 more Smart Citations
“…Finds of soft tissues of lingulids favour dysaerobic conditions. Lingulid burrows of reduced length (5-10 mm instead of 50-70 mm) were also found here (Miftakhutdinova, 2023), indicating that the primary sediment was compacted.…”
Section: Discussionsupporting
confidence: 53%
“…In the works of many researchers, the origin of clastic sediments was associated with continental alluvial processes (Danilova, 2008;Loscheva et al, 2017). Meanwhile, recent studies (Silantiev et al, 2022, Miftakhutdinova, 2023 have confirmed the marine origin of these sediments and linked them to transgressive episodes of the Devonian marine basin.…”
Section: Rate and Duration Of Sediment Accumulationmentioning
confidence: 87%
See 3 more Smart Citations